The impact of curcumin supplementation on inflammatory processes and recovery in athletes - Dominika Rosińska-Lewandoska; Dominika Lewandowska; Maria Morawska; Kinga Jarosz; Anna Wolff; Klaudia Kożuchowska; Szymon Gruszka; Marcelina Szewczyk; Dawid Pilarz; Julia Ufnal (Journal of Education, Health and Sport)
Introduction Athletes frequently encounter inflammation and muscle damage due to rigorous physical activities. These physiological processes, while necessary for adaptation, can delay recovery and hinder performance if excessive. Curcumin, a polyphenolic compound derived from turmeric, is recognized for its potent anti-inflammatory and antioxidant properties. This review examines the influence of curcumin supplementation on athletic recovery and inflammation, considering its mechanisms and applications.